Socio-demographic factors and suicidal behavior among the patients with psychiatric disorder attending outpatient department of a tertiary level hospital (Bangladesh Journal of Psychiatry, 2020)
The majority of suicides worldwide are related to psychiatric disorders. Overall, suicide rates vary concerning the age, gender, and socioeconomic status of the individual and the method of suicide. The objectives of the study were to find the socio-demographic factors and suicidal behavior associated with suicidal attempts in patients with psychiatric disorders. A cross-sectional, hospital-based, descriptive study was conducted among the patients attending the psychiatry outpatient departments (OPD) of the National Institute of Mental Health, Dhaka, Bangladesh. A total of 98 consecutive cases were included those who were at and above18year, have a definite psychiatric disorder and history of suicidal attempt. The data were collected by face-to face interview using semi structured questionnaire. The study identified that most of the patients were in the age group 21-30 years (53.1%), mean age± SD was 27.02±8.42, more in female (66.2%), housewives (35.7%), 57.1% were from an urban background and 35.7% of them studied up to SSC. The vast majority (73.5%) came from a nuclear family. Suicidal behavior revealed that mean suicidal attempt was 2.63±2.84, Communication intent was 20.4%, Suicidal note was put by10.2%, at home (90.8%),59.2%, sample choose day time and common method were hanging (25.5%) and medicine (22.4%). Help nearby in 72.4%, precaution against rescue was 18.4%, intent to die was 65.3% and hospitalization needed for 34.7% cases. Suicides can be prevented by early identification, diagnosis and proper intervention of psychiatric disorder among risk groups. Restricting access to means of suicide, by training caregivers, provide adequate follow-up care may reduce impulsive suicidal attempts.Bang J Psychiatry June 2018; 32(1): 14-18